Sexual and demographic determinants for herpes simplex virus type 2 among fishermen along Lake Victoria, Kenya. Issue 2 (20th December 2007) - O Ng'ayo, M; Bukusi, E; A Morrow, R; Rowhani-Rahbar, A; A Obare, B; Friedrich, D; Holmes, K K
Abstract : Objectives: To determine the prevalence and correlates of herpes simplex virus type 2 (HSV-2) seropositivity among fishermen along the shores of Lake Victoria in Kisumu district, Kenya. Methods: Sera from a random sample of 250 fishermen from 18 beaches were collected after a detailed sociodemographic interview. HSV-2 infection was tested by Kalon HSV-2 ELISA. Results: The HSV-2 seroprevalence was 63.9%. In multivariate analysis, fishermen were more likely to be infected with HSV-2 if they were HIV positive (prevalence ratio (PR) 1.27; 95% CI 1.06 to 1.52) compared with those testing HIV negative, were aged 18–20 (PR 0.49; 95% CI 0.24 to 0.99) and older than 40 (PR 1.66; 95% CI 1.30 to 2.14) years compared with those aged 21–25 years, perceived their last two sexual partners to have a sexually transmitted infection (STI; PR 1.27; 95% CI 1.06 to 1.52) compared with those who did not and were more likely to be circumcised (PR 1.49; 95% CI 1.19 to 1.86). Conclusions: HSV-2 seroprevalence is high among this population and is associated with HIV serostatus, age, perception about partner's STI status and circumcision.